Social media learning on Indonesian university students - Istiyanto, S. Bekti; Priyantono, Mochammad Bagus; Rifai, Muhammad Abdul Faiz; Wahyuningsih, Kartika; Fansyiari, Dzanun; Ramdhani , Lalu Gilang Obidia (Association for Scientific Computing Electrical and Engineering, 2021)
This study aims to compare social media as appropriate learning media for University students at Universitas Negeri Malang in the era of the covid-19 pandemic. The method used in this study is EUCS (End-user computing satisfaction) with a sample of 100 people. This study indicates that the google-classroom media is more in demand as a learning medium in terms of satisfaction by UM students. All the variable values are superior to the other two social media, namely Facebook and Schoology.